(untitled) (المجلة الدولية للبحوث العلمية, 2026)
This study involves the preparation of macrocyclic Schiff bases (R4-R8) through two steps, first step involves the preparation of macroacyclic Schiff bases (R1-R3) by the reaction of 3,5-diacety l-2,6-dimethyl-1,4-dihyropyridine DHP(R) with diamine derivatives (4-methyl 1,2-phenelene diamine, 1,4-phenelene diamine and hydrazine hydrate). The second step involves the synthesis of macrocyclic Schiff bases (R4-R8) via cyclization of acyclic schiff bases (R1-R3) which are further reacted with diketone derivatives (benzil, acetyl acetone and 3,5-diacetyl-2,6-dimethy l-1,4-dihyropyridine). The condensation reactions were carried out using both conventional reflux and microwave-assisted methods to evaluate the efficiency and yield of each approach. The synthesized compounds were analyzed and identified through proton nuclear magnetic resonance (1H NMR) spectroscopy and fourier-transform infrared (FT-IR) spectroscopy and nuclear magnetic resonance (13C NMR), indicating that the Schiff bases structures had been successfully formed, conforming the bonding arrangement and offering insight into the structural characteristics of the macrocyclic system. The cytotoxic effect of one of the synthesized compounds (R5) was assessed against MCF-7 breast cancer cell line using the MTT assay technique, whereas (R1, R2 and R5) were examined for their antibacterial activity using the agar well diffusion assay.